SDRs, Currencies, and Gold : Seventh Survey of New Legal Developments - Gold, Joseph (Pamphlet Series; Pamphlet Series, ;, 1987)
This paper presents the seventh survey of developments in international and national monetary law and practice involving special drawing rights (SDRs), currencies, and gold. The IMF has adopted three published decisions on surveillance over the exchange rate policies of members since the publication of Pamphlet No. 40 in 1983. The list of currencies remained unchanged because the share of the sixth largest exporter of goods and services in the world total (Italy) was below the share of the member with the fifth largest share (United Kingdom).